2016
DOI: 10.1371/journal.pone.0158314
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inflammatory and Cell Death Program Genes and Comet DNA Damage Assay Induced by Escherichia coli in Layer Hens

Abstract: Modern methods of industrial poultry and egg production systems involve stressful practices that stimulate Escherichia coli (E. coli) activity causing endotoxic shock. This investigation was conducted to evaluate the expression of pro-inflammatory cytokines and cell death program genes and DNA damage induced by E. coli in the brain and liver tissues of laying hens. A total of two hundred and ten H&N brown layer hens with 20 week age, were used in this research. First, preliminary experiments were designed (60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 76 publications
2
15
0
Order By: Relevance
“…The failure of thermoregulation process in the HS group may be due to the exergonic reactions of free radicals that are generated by heat stress [ 53 ]. In addition, the effects of heat stress on circulating corticosterone and MDA levels in the present study are similar to that obtained in previous works on both broilers and quail [ 16 , 54 ]. These results demonstrate that heat stress induced inflammation and lipid peroxidation of the quail as previously reported [ 12 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The failure of thermoregulation process in the HS group may be due to the exergonic reactions of free radicals that are generated by heat stress [ 53 ]. In addition, the effects of heat stress on circulating corticosterone and MDA levels in the present study are similar to that obtained in previous works on both broilers and quail [ 16 , 54 ]. These results demonstrate that heat stress induced inflammation and lipid peroxidation of the quail as previously reported [ 12 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results demonstrate that heat stress induced inflammation and lipid peroxidation of the quail as previously reported [ 12 , 55 , 56 ]. The excessive amounts of corticosterone may induce the fever that observed in the HS group [ 16 ]. Furthermore, the decline in fT 3 concentrations upon heat exposure is consistent with the reduction in feed consumption of the same quail group in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the massive meat production of broiler chickens make them continuously exposed to a wide range of potential stressors [ 1 ]. In our previous work [ 48 ], we found that endotoxin stress by E. coli infection to laying chickens markedly increased plasma corticosterone concentration by approximately 3 times more than normal chickens only 3 hr after E. coli injection. Such results and previous reports concluded that various forms of stress directly or indirectly activate the hypothalamic-pituitary-adrenal (HPA) axis and the release of corticosterone into blood [ 2 ].…”
Section: Discussionmentioning
confidence: 96%
“…Our results indicated that MC-LR did not significantly Mehaisen et al (2016) modulate the gene expression of caspase-3 and genes related to antioxidant activity. However, these genes tended to be upregulated in a dose-dependent manner after MC-LR exposure.…”
Section: Discussionmentioning
confidence: 59%